Diffuse idiopathic skeletal hyperostosis - appearance and diagnostics in Hungarian osteoarcheological materials - Paja, László (Acta Biologica Szegediensis, 2010)
Diffuse idiopathic skeletal hyperostosis (DISH) or Forestier’s disease appears in different skeletal elements, and usually characterized by the calcification of the right side anterior longitudinal ligament of the spine and by the ossification of entheses and ligaments at extra-spinal sites. Although the etiology of DISH is still unknown, but the presence of it seems to be connected with some metabolic diseases, like type II diabetes or obesity. On the basis of Resnick’s criteria, the recognition of DISH is not difficult, but in paleopathology, the osteoarcheological series’ different state of preservation may result in diagnostical uncertanity. This paper summarizes the results of the physical anthropological examinations carried out seven osteoacheological series from the Great Hungarian Plain, and points to those osseous alterations, which may be helpful in the diagnosis of DISH.